ANALISIS KETIDAKSEIMBANGAN BEBAN DAN HARMONISA PADA TRANSFORMATOR DISTRIBUSI MI 0096 PENYULANG ABIANBASE - Yoga Prasetya, I Wayan; Setiawan, I Nyoman; Dyana Arjana, I Gede (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUM, 2020)
MI 0096 Distribution Transformer is one of the transformers supplied by Abianbase Feeders. The MI 0096 distribution transformer has a capacity of 100 kVA with a daytime load of 48,5 kVA and a nighttime load of 50,81 kVA. Unequal single-load loads on the transformer result in unbalanced loads on the transformer MI 0096 and the use of non-linear loads results in harmonic distortion on the transformer MI 0096. In this study, carried out a comparison of load imbalance and harmonics that occur during the day and night. The results of the analysis found that the percentage of load imbalance in the MI 0096 Distribution Transformer is classified in poor condition that exceeds 25% with the percentage of load imbalances during the daytime at 28,74% and at noon 30,28%. THDv on the MI 0096 Transformer is within the allowable limit of below 5% with THDv at 1,7% during the day and 1,9% at night. THDi in the MI 0096 Distribution Transformer exceeds the allowable standard which exceeds 8%, with THDi during the day 17,5% and at night 24%. Losses caused by the THDi in the MI 0096 transformer have increased along with the increase in THDi in the transformer. Losses without THDi are 0,5 kW, while total losses after being affected by THDi are 5,79 kW during the day and 11,01 kW at night.